(untitled) (The GIST, 2024)
Song is a creative works that created by someone to express what inside their mind to other people. One of the interesting songs is a song by Mili entitled “Ga1ahad and Scientific Witchery” where the song itself is a storytelling. In every line will have a theme, where the theme will be the main idea of the clause. The aim of this research is to study about theme and rheme in Mili’s song. This research uses a qualitative method, and the sample for this research is the lyrics of “Ga1ahad and Scientific Witchery”. From the results of this results, can be found the most used theme is topical theme, meanwhile for the most used type theme is topical theme. Theme from every clause that found really determine the real meaning from the lyrics.